PEMAKNAAN KHALAYAK TERHADAP PERAN PEREMPUAN DALAM FILM SELESAI - Renata Wardani; Hapsari Dwiningtyas Sulistyani; Hedi Pudjo Santosa (Interaksi Online, 2023)
The Selesai movie had uncovered controversy in the middle of 2021 because it was considered problematic for 3 female roles simultaneously. This study aims to understand and describe how the audience interprets the role of women as wife, mother and mistress in the Selesai movie. This study uses Stuart Hall's Audience Reception Theory. John Fiske's The Codes of Television is used to analyze the dominant meaning and Stuart Hall's reception analysis method is used to determine the meaning position of the audience. Data collection was carried out using in-depth interviews with the subjects in this study, male or female viewers who had watched the film Finish at least once. The results of the study show that in Preferred Reading, the Dominant Ideology is shown in this film is Patriarchal Ideology. Women are portrayed as guilty, selfish, weak and sexual objects. The informant brought it up. However, in the diversity of meanings there are alternative meanings that emerge, the wife is interpreted as a partner and complement of the family that still depend on the husband but it is also found that the meaning of the wife is interpreted as being able to choose differences including in the sphere of sexuality and the economy. The diversity of meanings related to mother is still dominant in child marriage, some see this as having good intentions or even disturbing their child's marriage. Mistresses are interpreted as having the right to fulfill what is not owned by a legal wife, there are those who interpret it only in the sexual sphere or in all aspects including emotional support. This study found that the dominant ideological films were not always followed by informants. Informants who reject the construction of women in the film are motivated by life experiences, new knowledge and the environment of the informants.